Overview of Circular Structures of Various Origins and Sizes in Egypt as a Contribution to Natural Hazard Data Mining Based on Remote Sensing Data and Geoinformation Systems (GIS) Analysis - Theilen-Willige, Barbara (Prevention and Treatment of Natural Disasters, 2023)
This study is focused on the detection and typification of circular features with different sizes, origins, and states of erosion as well as on their surrounding tectonic setting, as well as on their impact on the environment and on the occurrence of natural hazards based on different satellite data of Egypt. Sentinel 2, Landsat and ASTER images and Sentinel 1- and ALOS L-band Phased Array Synthetic Aperture Radar (PALSAR)-radar data make it possible to identify larger ring structures as well as smaller circular features like maars or sinkholes in karst areas. Evaluations of the various satellite data contribute to the systematic and standardized inventory ring structures, most of which are related to magmatic intrusions. Such an inventory is a prerequisite for hazard preparedness and should be part of natural hazard data mining integrated into a Geo Information System (GIS). Mapping traces of volcanic activities (craters, maars, cones) is essential as a contribution to land use planning. By gathering the data and integrating the knowledge of the different ring structures in standardized GIS data base one of the many steps towards hazard preparedness and adapted land use planning can be achieved. Circular features are often buried by aeolian and fluvial sediments and become only visible on radar images or on Landsat or ASTER RGB images combining thermal bands. Larger ring structures have not only an influence on groundwater flow but also on geodynamic activity (earthquakes and related secondary effects).